Sosialisasi Hukum Ketenagakerjaan Berdasarkan Undang-Undang Ketenagakerjaan No 13 Tahun 2003 - Salman; Chandra, Febrian (PT. Meja Ilmiah Publikasi, 2024)
The socialization of labor law based on Law No. 13 of 2003 is crucial in providing the public with an understanding of workers' rights and obligations. The rapid growth of the industrial sector has created vast job opportunities, leading many workers to migrate to industrial areas in search of better employment opportunities and fair wages. However, a lack of awareness regarding labor regulations often results in ignorance of fundamental rights such as minimum wages, social security, and termination of employment (PHK) policies. Therefore, STIH YPM conducted a labor law socialization program for the people of Sungai Ulak Village to educate them on labor regulations. The results indicated an increased awareness among participants regarding employment laws and the importance of understanding work contracts before entering industrial employment. Through this initiative, the community is expected to gain a deeper understanding of their rights and obligations as workers, helping them avoid potential exploitation in the workplace.